MEKANISME DAN IMPLIKASI DESENTRALISASI PELAYANAN PUBLIK TERHADAP WEWENANG PEMERINTAH DAERAH DITINJAU DARI UNDANG-UNDANG NO. 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK - Pratiwi, Dian Kus (Jurnal Yuridis, 2017)
The legal purpose is to deepen knowledge of local governance and decentralization principles in public service ministry in terms of UU No. 25 Tahun 2009 and find out the mechanisms and implications decentralization of the local government. This research is a normative law prescriptive with normative juridical methods, by researching secondary data and then analyzed with the interpretation of the mechanisms and implications public services to local government authority in terms of the Public Service Act. Results showed that the implementation of public service decentralization motivated by devolution of power from central to local government. Arrangements for public services through decentralized is according to the principles in UU No. 25 Tahun 2009. Implementation shows that has some positive and negative implications